Rotating-shaft high-torsion-resistance wood cutting machine - ZHU DEJIN (2015)
The invention discloses a rotating-shaft high-torsion-resistance wood cutting machine. The rotating-shaft high-torsion-resistance wood cutting machine comprises a cutting machine motor and is characterized in that the side face of the cutting machine motor is provided with a first power transmitting shaft, the end of the first power transmitting shaft is provided with a power shaft converter, and the other side of the power shaft converter is provided with a cutting edge; and the peripheries of the cutting machine motor and the cutting edge are provided with damping protection rings respectively, and power shaft converters are made of high-strength cast silicon steel. Due to the fact that the two power shaft converters are arranged on the rotating-shaft high-torsion-resistance wood cutting machine, the length of a power shaft is reduced greatly, wear caused by torsional force is lowered effectively, the power of the cutting machine is improved, and the service life is prolonged. Due to the fact that the peripheries of the cutting machine motor and the cutting edge are provided with the damping protection rings, the vibration wear of the motor can be lowered effectively, and long-time efficient working of the motor is kept. Due to the fact that the power shaft converters are made of the high-strength cast silicon steel, and stress redistribution caused by stress deformation is avoided.